TO THE PROBLEM OF HIGH-VOLTAGE EQUIPMENT NOISE DIAGNOSTICS - N. I. Ignatev (Известия высших учебных заведений: Проблемы энергетики)
Application possibilities of electrical power equipment noise diagnostics are shown. The diagnostics possesses increased depth and the enlarged reliability of diagnosing. Main guidelines of the technique based on determination of external and internal constructive elements deficiencies are described. Stages of obtaining information about full deficiency of the equipment are explained in detail on the example of diagnosing of five power autotransformers with various term of operation. The received results well correspond with the data obtained by other diagnostic methods.